Dehydration, Packing and Storage Studies of Fruits (Banana, Jack and Mango) - Kuber Singh K (Department of Processing Technology, College of Horticulture, 1983)
A series of experiments were conducted at the College of Horticulture, Vellanikkara, with the objective of proposing a suitable method of preservation and storage of fruits, viz., banana, mango and jack. The fruit material prepared by peeling and cutting were dehydrated by mechanical drying for 80 - 87 hours, since sundrying was found to be unsatisfactory even after 25 days of drying. The dried materials, both as chips and powder were packed in craft paper bags, butter paper bags, polythene bags and polypropylene bags and were stored in both open air as well as closed conditions. The samples stored in open air conditions deteriorated in quality after a short span of storage and first sign of fermentation was observed by 50th day. The packages kept in closed chamber remained without deterioration throughout the period of study. The analysis of quality constituents such as moisture level, total soluble solids, total sugars, reducing sugars and titrable acidity indicated that the minimum change from the zero storage conditions can be obtained if the materials are stored in polythene or polypropylene bags, among the four packing materials tried. The syrup strength for reconstituting the stored materials were standardised as 25% for mango and banana and 30% for jack fruit. The reconstituted materials were organoleptically evaluated both as such and as a preparation containing jaggery, coconut milk, spices etc. and it was found that banana chips remained acceptable up to 110 days in polythene and polypropylene bags and the powder remained good throughout. The mango chips were acceptable up to 130 days in these packages while powder was good even after 190 days of storage. The jack fruit chips stored in polythene and polypropylene bags were good up to 150 days while the powder remained acceptable even after 190 days. In all the cases where craft paper and butter paper bags were used, the fruit samples could not be stored so successfully as observed in the polythene and polypropylene bags.